2018
DOI: 10.1152/ajprenal.00609.2017
|View full text |Cite
|
Sign up to set email alerts
|

Combination exposure of melamine and cyanuric acid is associated with polyuria and activation of NLRP3 inflammasome in rats

Abstract: The molecular mechanisms of melamine-induced renal toxicity have not been fully understood. The purpose of the study aimed to investigate whether melamine and cyanuric acid induced NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation in the kidney, which may contribute to abnormal water and sodium handling in a rat model. Wistar rats received melamine (Mel; 200 mg·kg body wt·day), cyanuric acid (CA; 200 mg·kg body wt·day), or Mel plus CA (Mel + CA; 100 mg·kg body wt·day, each) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Our recent studies 36 , 37 have revealed an inhibitory role of NLRP3 inflammasome in the regulation of aquaporins in the kidneys. In order to unravel the potential mechanism by which cholesterol may affect the protein expression of AQP2, the protein expression profiles of ASC, an adaptor of NLRP3 inflammasome, were examined in the kidney specimens of patients with or without atorvastatin treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent studies 36 , 37 have revealed an inhibitory role of NLRP3 inflammasome in the regulation of aquaporins in the kidneys. In order to unravel the potential mechanism by which cholesterol may affect the protein expression of AQP2, the protein expression profiles of ASC, an adaptor of NLRP3 inflammasome, were examined in the kidney specimens of patients with or without atorvastatin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Next we examined a potential mechanism by which cholesterol may impact the protein expression of AQP2. Our recent studies 36 , 37 have revealed an inhibitory role of NLRP3 inflammasome in the regulation of aquaporins of the kidneys. As expected, the protein expression of ASC monomer, cleaved Caspase-1 (p20) and cleaved IL-1β in the kidneys was found to be upregulated in wild type mice on a HFD; while in nlrp3 -/- mice, the HFD seemed to have failed to induce significant changes in the protein expression of ASC, Caspase-1 (p20) and cleaved IL-1β expression (Figure 3 A and B).…”
Section: Resultsmentioning
confidence: 99%
“…For semiquantitative immunoblotting and immunocyto chemistry, previously characterized affinity-purified polyclonal antibodies to AQP2 and AQP3 were used (Wang et al, 2018). Antibodies to AQP1 were obtained from BOSTER (Wuhan, China); antibodies to IL-1β, p-NF-κB p65, and NF-κB p65 from Cell Signaling Technology; caspase-1 from Abcam; antibodies to ASC from Santa Cruz; and NLRP3 from Novus.…”
Section: Methodsmentioning
confidence: 99%
“…The left kidney blocks containing all kidney zones were dehydrated and embedded in paraffin. For immunoperoxidase microscopy, sections (4 μm thick) cut from paraffin-embedded kidney samples were used for immunostaining of AQP2 (Wang et al, 2018). Briefly, after dewaxing and rehydration, a microwave pretreatment in citrate buffer (pH 6.2) was performed to unmask antigens present in the renal tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation